The application of discrete choice experiments in cost-effectiveness studies to assess the benefits of sensor-augmented insulin pump therapy for the treatment of type 1 diabetes - Barnett, N.; Geelhoed, E.; Davis, E.; Jones, T.; De Bock, M.; Smith, G.; Norman, Richard (2016)
Background and Aims: Diabetes Mellitus affects over 630 million people worldwide and is directly attributed to 1.5 mil- lion deaths annually. Few studies have been conducted to determine the cost-effectiveness of gold-standard type 1 diabetes treatment resulting in low uptake among countries that do not provide subsidised access to patients. Discrete choice experiments (DCE) are an innovative measurement tool applied in a number of fields, however their application in health treatment lags. DCEs can be used to explore preferences towards alter- native treatment options and to determine relative cost-effectiveness using a holistic measure of relative attributes in the decision-making process. Method: A literature review was undertaken to identify the application of discrete choice experiments to evaluate preferences in type 1 diabetes treatments. Search terms were restricted to studies on type 1 diabetes but were not limited on any other basis. Results: Three papers contained the terms ‘discrete choice experiment’ and ‘type 1 diabetes’ from relevant databases. At present there are no studies that analyse the cost-effectiveness of type 1 diabetes treatment using a discrete choice experiment methodology. Conclusion: A significant gap in the literature suggests there is scope for a discrete choice experiment to be conducted with patients and parents of children suffering from type 1 diabetes. An applied DCE would contribute valuable insights into the benefit measurement of gold-standard therapies and may improve access if cost-effectiveness is demonstrated